Mapping Gender Educational Policies in STEM Areas in the Context of the New Brazilian High School Education - Lima, Waleska Gonçalves de (2023)
This text presents an ongoing research that relates the policy mapping activity aimed at promoting gender-related issues in STEM (Science, Technology, Engineering, and Mathematics) conducted by the ELLAS research network (Equality in Leadership for Latin American STEM) to the Brazilian New High School policy. Through document analysis related to the policy, it is possible to identify indications of the gender demand in STEM within the national policy, stemming from the loan agreement with the World Bank.